A Study of Parameters Affecting the Solvent Extraction-Flocculation Process of Used Lubricating Oil - Hussein Qasim Hussein; Ali Laith Abdulkarim (Journal of Engineering, 2017)
The aim of this study was to investigate the effect of operating variables on, the percentage of removed sludge (PSR) obtained during re-refining of 15W-40 Al-Durra spent lubricant by solvent extraction-flocculation treatment method. Binary solvents were used such as, Heavy Naphtha (H.N.): MEK (N:MEK), H.N. : n-Butanol (N:n-But), and H.N. : Iso-Butanol (N:Iso:But). The studied variables were mixing speed (300-900, rpm), mixing time (15-60, min), and operating temperature (2540, oC). This study showed that the studied operating variables have effects where, increasing the mixing time up to 45 min for H.N.: MEK, H.N.: n-Butanol and 30 min for H.N.: Iso-Butanol increased the PSR, after that percentage was decreased; increasing the mixing speed for all the studied solvents up to 700 rpm increased the PSR, after that the percentage was decreased, while increasing the operating temperature decreased the PSR for all the solvents. This study has resulted in reasonably accurate multivariate process correlation that relates the removed sludge percentage to the process variables. The determination coefficients (